Lord of lark and lightning: reassessing Celtic Christianity's ecological emphases - Martin, Bruce (The journal of religion & society, 2004)
A growing literature explores relationships between religion, ecology, and environmental stewardship. In Christian writings, Celtic Christianity has been proposed as exemplary for contemporary Christians seeking harmonious relationships among humanity, God, and nature. The accuracy of descriptions in this recent literature of ecological values perceived in Celtic Christianity requires critical evaluation against the evidence. This paper aims to investigate the key themes contemporary Christian writers identify as defining characteristics of early Celtic Christianity and evaluates these against primary sources of early Celtic literature. A careful reading of early Celtic literature reveals an ambiguous understanding of relationships between humanity, nature, and God.